PENGARUH KEPEMIMPINAN DAN PEMBERIAN UPAH TERHADAP KINERJA KARYAWAN DI MASA PANDEMI COVID-19 PADA CV. MULTAZAM SITUBONDO - Nurul Imam Rozali; Ahmad Hafas Rasyidi; Lisma Dian Kartika (Relawan Jurnal Indonesia, 2021)
This study aims to determine the effect of leadership and remuneration on employee performance during the covid-19 pandemic at CV Multazam Situbondo in 2021. This study uses Ex Post Facto research. The population in this study were all employees of CV. Multazam Pecaron, totaling 39 people. Data collection in this study was carried out using observation, interviews, questionnaires, and documentation and then analyzed by multiple regression analysis. From the results of data analysis obtained using the multiple regression analysis formula, the R-count value is compared to the R-table, and the results of the comparison of the R-table with a significance level of 5% with a sample of 39 people obtained R-table = 0.329 while the major hypothesis Ry(1 ,2) = 0.736. using the significance test. The calculation of the analysis of variance of the regression line obtained a Freg of 21.387. And when consulted with the F table for db = 2 and db = 36 with a significance level of 5%, it was obtained 3.26. the effectiveness of the regression line is obtained by 54.31% %. This means that the effective contribution of the overall predictors of student learning outcomes contributed 54.31% and the variables (other factors) that were not examined were 100% 54.31% = 45.69%.